Research progress of death education for cancer patients (癌症患者死亡教育的研究进展) - ZHU Yalin (朱雅麟); SHI Linlin (石琳琳); WU Siyu (吴思雨); ZHANG Mengling (张梦玲); SU Huiling (苏慧玲); CHAI Shouxia (柴守霞); YANG Liu (杨柳) (Journal of International Translational Medicine Limited, 2023)
By introducing the concept of death education, comparing the death education needs of cancer patients at home and abroad, death education evaluation tools, and summarizing the methods and existing problems of death education, this paper aims to provide a theoretical basis for the development of death education for cancer patients in China. (本研究通过介绍死亡教育概念, 对比国内外癌症患者的死亡教育需求, 总结死亡教育评估工具, 分析死亡教育方法及存在的问题, 旨在为国内癌症患者死亡教育发展提供理论依据。)